A CRITICAL REVIEW ON THE DISCUSSION OF DEVELOPING SPEAKING SKILLS THROUGH TASK BASED MATERIALS - Ika Handayani; Eri Rahmawati; Ledy Nurlely (Indonesian EFL Journal, 2022)
This is a critical review elaborated on the strengths and the weaknesses of the article content. The Purpose of the Study. It is aimed to review critically on the discussion of Developing Speaking Skills Through Task Based Materials by relating those findings with the theories, books and articles in reputated journal. Research Method. This study used Systemic Literature Review to identify, study, evaluate, and interpret the research about interesting phenomenon with certain relevant research. Every data is linked to studies which have the same discussion either from theories, books and relevant articles published in reputated journal. The data is analyzed using Content analysis to analyze the content of the article as the main data. The source of data were taken from the whole content of the article that discussed about processing action on improving speaking through the implementation of Task Based Material. Main Findings. The findings showed that there were some unclear discussions about abstract information; moves organization in introduction; lack of current and relevant studies and theories; unsystematic findings related to the proposed research questions; and the terms used in the article. As the conclusion, this critical review has given informative and suggested references to support the ideas and views of the articles from reputated and current journals and recent books started from 2003 (telling the story of Task Based language teaching implementation and theories) to 2021 (suggesting the steps in developing materials through Task Based materials).Keywords: speaking skills; task based materials; critical review